Vrātya or Ancient Indo-Aryan Violence? - Chiara Neri; Tiziana Pontillo (Cracow Indological Studies, 2024)
Jaiminīya-Brāhmaṇa (JB) II 225 and Pañcaviṃśa-Brāhmaṇa (PB) XVII 1.9 have been authoritatively interpreted by Falk (1986: 29–30) as evidence that the Vrātyas behaved in a peculiarly aggressive way. The present study puts forward the hypothesis that such violence was not a distinguishing feature of the Vrātyas, but an inherited common trait of the Indo-Aryan culture, which, for example, is well documented in its strong warrior tradition, in clashes between clans and families for dynastic reasons, in the frequent use of curses and other acts of verbal violence and in the ritual violence of bloody sacrifices. These various deep-rooted cultural patterns might all have stemmed from the original highly competitive social organization of the Indo-Aryan people. The way in which Vrātyas selected their leader, regardless of his birth status, in line with Buddhist meritocracy, also proves to be in line with this assumed competitiveness of the origins. This paper concentrates on the violence inherent in the Vrātya dialogues and their dramatic consequences. These dialogues are compared here with the Old and Middle Indo-Aryan “verbal contests” on the basis of Vedic and Pali texts, in the wake of work by Witzel (1987) and Manné (1990), who singled out relevant schemes and formulas in both the Brahmanical and Buddhist sources. Indeed, the earliest sources provide ample evidence of agonistic sapiential debates (the so-called brahmodyas), in which the loser is forced to submit to the winner or even undergo a much worse punishment.